Impact of tribocorrosion and titanium particles release on dental implant complications - A narrative review - Waad Kheder; Sausan Al Kawas; Khaled Khalaf; A.R. Samsudin (Elsevier, 2021)
Titanium particles as a product of degradation have been detected in periimplant oral tissues and it has been assumed that implants were the source of these particles. Periimplantitis sites had higher concentrations of particles in comparison to healthy implant sites. Several factors have been identified in the degradation of dental implant surface, such as mechanical wear, contact with chemical agents, and the effects of biofilm adhesion. Titanium particles silently prompt the immune-system activation and generate a pro-inflammatory response in macrophages, T lymphocytes and monocytes. During the activation, inflammatory cytokines are released including, granulocyte-macrophage colony-stimulating factor (GM-CSF), prostaglandin, and TNF-α, IL-1β, IL-6. The nanoparticles depict unique features such as high level of biological reactivity and potentially harmful compared to microparticles since they have a relatively greater surface area to volume ratio. Allergic response to titanium as a cause of implant failure has not been well documented. Evidence demonstrating biological complication due to titanium particles release includes peri-implant tissue inflammation that lead terminally to implant loss. There is a biological probability for a relation between the presence of titanium particles and ions, biological complication, and corrosion, but there is no justifiable evidence for unidirectional series of causative actions.